Third Five-Year Plan Madras State Draft Outline - Planning Commission (Planning Commission, 1960)
The outlay ou the National Plau falls into three broad sectors according to tne agencies which are responsible for the implementation of the various schemes covered by the Plan. the first one is the Central Sector made up of the major development works undertaken by the Central Government such as the installation of the new steel plants, heavy machinery plants, fertilizer units, coal mining schemes, oil exploration and refineries, improvements to major ports and railways, etc. Next comes the State Sector comprising of schemes for the development of agriculture, power, communications, social services such as education, health, rural uplift, etc.
Finance (P and D) Department Government of Madras